Narzędzia zarządzania ryzykiem : Perspektywa strategiczna - Sus-Januchowska, Aleksandra (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The aim of this report is to present the instruments which managers could use in strategic risk factors. The article concentrates on the strategic risk category; it defines strategic risk, strategic risk management, and shows how to organize operations in risk conditions by using the risk exposure calculator and real options analysis. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 219-225